New variants including ARG1 polymorphisms associated with C-reactive protein levels identified by genome-wide association and pathway analysis. - Nadimuthu Vinayagamoorthy; Hae-Jin Hu; Seon-Hee Yim; Seung-Hyun Jung; Jaeseong Jo; Sun Ha Jee; Yeun-Jun Chung (PLoS ONE, 2014)
C-reactive protein (CRP) is a general marker of systemic inflammation and cardiovascular disease (CVD). The genetic contribution to differences in CRP levels remains to be explained, especially in non-European populations. Thus, the aim of this study was to identify genetic loci associated with CRP levels in Korean population. We performed genome-wide association studies (GWAS) using SNPs from 8,529 Korean individuals (7,626 for stage 1 and 903 for stage 2). We also performed pathway analysis. We identified a new genetic locus associated with CRP levels upstream of ARG1 gene (top significant SNP: rs9375813, Pmeta = 2.85×10(-8)), which encodes a key enzyme of the urea cycle counteract the effects of nitric oxide, in addition to known CRP (rs7553007, Pmeta = 1.72×10(-16)) and HNF1A loci (rs2259816, Pmeta = 2.90×10(-10)). When we evaluated the associations between the CRP-related SNPs with cardiovascular disease phenotypes, rs9375813 (ARG1) showed a marginal association with hypertension (P = 0.0440). To identify more variants and pathways, we performed pathway analysis and identified six candidate pathways comprised of genes related to inflammatory processes and CVDs (CRP, HNF1A, PCSK6, CD36, and ABCA1). In addition to the previously reported loci (CRP, HNF1A, and IL6) in diverse ethnic groups, we identified novel variants in the ARG1 locus associated with CRP levels in Korean population and a number of interesting genes related to inflammatory processes and CVD through pathway analysis.